2012
DOI: 10.5121/ijsc.2012.3304
|View full text |Cite
|
Sign up to set email alerts
|

A Rough Set based Fuzzy Inference System for Mining Temporal Medical Databases

Abstract: The main objective of this research work is to construct a Fuzzy Temporal Rule Based Classifier that uses fuzzy rough set and temporal logic in order to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This showed that for decision attributes, these four attributes were sufficient to maintain the classification ability of the information system. By sorting the reduced decision table, the rules of precision >0.75 and coverage >0.05 were selected [30]. Finally, the typical diagnostic rule table is shown in Table 4.…”
Section: Classification Rule Extractionmentioning
confidence: 99%
“…This showed that for decision attributes, these four attributes were sufficient to maintain the classification ability of the information system. By sorting the reduced decision table, the rules of precision >0.75 and coverage >0.05 were selected [30]. Finally, the typical diagnostic rule table is shown in Table 4.…”
Section: Classification Rule Extractionmentioning
confidence: 99%
“…The membership function is determined with the expert concern. Accordingly, the rule set will be generated and the decision making will be performed [11] [12]. The fuzzy based interference system is a rule based classifier in which temporal algebra is used to generate the fuzzy rules.…”
Section: Fuzzy Rule Based Decision Makingmentioning
confidence: 99%